Responsive, Water‐Soluble Europium(III) Luminescent Probes. Issue 42 (22nd June 2017) - Shuvaev, Sergey; Starck, Matthieu; Parker, David
Abstract: The design principles, mechanism of action and performance of europium(III) complexes that serve as strongly emissive and responsive molecular probes in water are critically discussed. Examples of systems designed to assess pH, selected metal ions and anions, including chiral species, as well as selected small molecules and biopolymers are considered, and prospects evaluated for improved performance in more complex biological media such as in bio‐fluids and within living cells. Modulation of the emission spectral form, lifetime and degree of circular polarisation can be used to quantify the spectral response and permit calibration. Abstract : Perturbation of the bright, red emission of europium coordination complexes is being used to signal real‐time chemical changes in vitro and in cellulo. By understanding their key design principles and their mode of action, new probes for cations, anions, pH and for the local chiral chemical environment can be created. In this critical Minireview, selected examples are highlighted emphasising the need to take care in establishing reversibility of action and in calibration.